(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This work presents and discusses the dramaturgical adaptation process that gave rise to the play Era uma vez en la fronteira selvagem. The article describes will be described part of the theatrical creation process, shaped by intercultural experiences, and how the adapted theatrical script has incorporated these experiences, transformed into text, including through independent and collaborative writing exercises, which brought to the play contributions from theater artists and their experiences with Portuguese, Spanish and Indigenous languages (Kaiowá). Also explored, the shared creation method will be explored, in which dramaturgical, scenic, and musical proposals have influenced one another.